Caracterização de filmes finos por reflectometria de raios x - Silva, Adicleison Véla da (2013)
This work deals with the study and the understand about the technique of X-ray reflectometry applied to the analysis of thin films. Accordingly thin films were chosen with a unique chemical composition (Ag, Cr and Nb) with different nominal thickness produced by two different equipments, but with the same technology (sputtering). For the curves of reflection, was used an X-ray diffractometer Rigaku RINT2000/PC, where small changes were necessary for correct implementation of the measurements. These results were analyzed using two variations of Parratt formalism (PARRATT, 1954), utilizing a complete software IILXRR2013 (MACHADO, 2013) that allows the simulation of reflectometry curves for thin films including roughness effects based on (CROCE, DEVANT, et al., 1970) and another, called simplified method, based on evaluation of the positions of maximum of franjes with the respect to the order of reflection. The latter being an excellent alternative for a prior analysis of the thickness of thin films. The results showed that is possible, using minor experimental modifications to obtain a good evaluation of layer thicknesses of various films, extending its use as a good thin films qualifier in general